Physical Test of Fennel Leaf Ethanol Extract Gel Formulation (Foenicullum vulgare mill.) - Abdul, Ahwan; Mei, Enjelina Sinta; Diana; Rosyadah, Hafidz; Salsabila , Fathin (Journal of Nutraceuticals and Herbal Medicine, 2025)
Fennel is a plant that is widely used as food and traditional medicine, the parts of the plant that are often used are the fruit and leaves. This plant has many pharmacological activities, including being antibacterial. The aim of this research was to test the physical properties of ethanol extract gel preparations of fennel leaves with various formulas. The method used in this research is experimental research carried out in the laboratory using four formulas (F1, F2, F3 and F4) with different concentrations of fennel leaf extract from 1%, 2%, 3% and 4%. The research results obtained in the organoleptic tests met the requirements for each formula, while the physical tests (homogeneity, pH, viscosity, spreadability and stickiness tests) for Formula 1 (1%) and Formula 2 (2%) met the physical test requirements. Meanwhile, in Formula 3 (3%) and 4 (4%) the physical tests in the homogeneity, viscosity and adhesion tests did not meet the requirements and for the pH test and spreadability test they met the requirements. The results of statistical tests using the ANOVA test on the viscosity, adhesion and spreadability tests had significant differences (p<0.05). These results can be concluded that formulas 1 and 2 are preparations that meet the requirements as gel preparations compared to formulas 3 and 4.